2020
DOI: 10.1016/j.eats.2020.08.014
|View full text |Cite
|
Sign up to set email alerts
|

The “Motionless Gastrocnemius”: A Reliable Sign for Safe Graft Harvesting

Abstract: Difficulties in graft harvesting of the hamstring have been the topic of many studies. These difficulties are related to the aponeurotic or fibrous attachments of the hamstrings with the medial head of the gastrocnemius muscle, soleus muscle, and leg fascia. Freeing the graft from these attachments is important because insufficient release prior to stripper insertion can lead to premature transection or amputation. We describe a reliable intraoperative physical examination sign to help understand the sufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Harvesting and reconstruction using an ADM tendon was first described as an open procedure, which is also the safest one [6]. While blunt finger dissection might be sufficient for freeing other grafts [3], visualization and sharp dissection might be required to free the ADM tendon proximally [6, 9]. Clinical experience has shown that using a stripper that allows to cut the tendon at a desired length is safer and has been shown to minimize complications [6, 7] and that direct visualization of the tendon (through a camera or by a bigger incision) together with the stripper allows for accurate visualization of surrounding structures and could potentially prevent injury to neurovascular structures.…”
Section: Discussionmentioning
confidence: 99%
“…Harvesting and reconstruction using an ADM tendon was first described as an open procedure, which is also the safest one [6]. While blunt finger dissection might be sufficient for freeing other grafts [3], visualization and sharp dissection might be required to free the ADM tendon proximally [6, 9]. Clinical experience has shown that using a stripper that allows to cut the tendon at a desired length is safer and has been shown to minimize complications [6, 7] and that direct visualization of the tendon (through a camera or by a bigger incision) together with the stripper allows for accurate visualization of surrounding structures and could potentially prevent injury to neurovascular structures.…”
Section: Discussionmentioning
confidence: 99%